2017
DOI: 10.1148/rg.2017170090
|View full text |Cite
|
Sign up to set email alerts
|

Adventures and Misadventures in Plastic Surgery and Soft-Tissue Implants

Abstract: Soft-tissue augmentation and implants are increasingly seen by the radiologist as more techniques emerge for a variety of indications and locations. Some surgical and implant procedures are performed for purely cosmetic reasons in otherwise healthy patients seeking to improve their body image, and some are performed for reconstruction after cancer or other chronic illnesses. Abdominoplasty, liposuction, and autologous fat grafting can be performed for abdominal and gluteal contouring. Injection of liquid injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 66 publications
(119 reference statements)
0
22
0
Order By: Relevance
“…However, clearly, such interventions can be fraught with unexpected and undesirable consequences. 1,8 Silicone injection for girth enhancement can result in drifting, distant migration, swelling, penile distortion, and granulomatous reactions. This material can damage blood vessels and nerves, resulting in decreased sensation and erectile dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…However, clearly, such interventions can be fraught with unexpected and undesirable consequences. 1,8 Silicone injection for girth enhancement can result in drifting, distant migration, swelling, penile distortion, and granulomatous reactions. This material can damage blood vessels and nerves, resulting in decreased sensation and erectile dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 The use of implants for temporal augmentation was investigated because previous traditional modalities, such as injectable fillers and fat grafts, had less predictable survival time, limited availability, and decreased pliability. 34,35 However, implants present their own challenges to clinicians, including difficulty in identifying good surgical candidates, improper implant size selection, and inappropriate implant location placement, as well as migra-tion and extrusion. 35,36 Traditional complications are also possible, including seroma, hematoma, and infection.…”
Section: Implantsmentioning
confidence: 99%
“…34,35 However, implants present their own challenges to clinicians, including difficulty in identifying good surgical candidates, improper implant size selection, and inappropriate implant location placement, as well as migra-tion and extrusion. 35,36 Traditional complications are also possible, including seroma, hematoma, and infection. 36 In our review, we identified studies using methyl methacrylate (MMA) and polytetrafluoroethylene (PTFE) implants for aesthetic temporal augmentation.…”
Section: Implantsmentioning
confidence: 99%
“…However, skin and soft tissue infections are common with rapid growers. 1 Here, we report the case of a previously healthy patient, who developed an infection with Mycobacterium agri (a rapidly growing nontuberculous bacillus) that was isolated from purulent samples. Treatment of NTM is challenging due to multiple antimycobacterial drug resistances.…”
Section: Introductionmentioning
confidence: 99%